2020
DOI: 10.3389/fgene.2020.00756
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Carbohydrate Esterase Families 1 and 10 in Oomycetes

Abstract: Carbohydrate-active enzymes (CAZymes) are a cornerstone in the phytopathogenicity of filamentous microbes. CAZymes are required for every step of a successful infection cycle-from penetration, to nutrient acquisition (during colonization), to exit and dispersal. Yet, CAZymes are not a unique feature of filamentous pathogens. They are found across eukaryotic genomes and including, for example, saprotrophic relatives of major pathogens. Comparative genomics and functional analyses revealed that CAZyme content is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The function of CEs is to participate in the metabolism of carbohydrate esters ( Armendariz-Ruiz et al., 2018 ). Genes putatively coding for the CAZyme families of carbohydrate esterases CE1 and CE10 have been suggested to have lifestyle-specific gene expression patterns ( de Vries and de Vries, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The function of CEs is to participate in the metabolism of carbohydrate esters ( Armendariz-Ruiz et al., 2018 ). Genes putatively coding for the CAZyme families of carbohydrate esterases CE1 and CE10 have been suggested to have lifestyle-specific gene expression patterns ( de Vries and de Vries, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…C. eragrostidis C52 was rich of CAZymes responsible for colonization cycle, nutrient acquisition and dispersal that are shaped by utilized substrate, lifestyle, and host preference 27 . A recent study proved that the repertoire of CE1 and CE10 genes was significantly reduced in biotrophic pathogens 28 . As it stands, plant-derived Curvularia strains ( C. lunata CX-3, C. lunata W3, C. geniculata P1, C. geniculata W_3) and human-derived strains ( C. kusanoi 30M1, C. papendorfii UM 226) had an average CE10 of 16 genes.…”
Section: Discussionmentioning
confidence: 99%
“…For pathogenic fungi invading a host, carbohydrate-active enzymes (CAZymes) play important roles in penetration, colonization, exit, and dispersal during infection progress [ 30 ]. Several studies have indicated that massive CAZyme-encoding genes are activated during infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%